Sistem Pengambil Keputusan Pemilihan Brand CCTV Terbaik Menggunakan Metode Simple Additive Weighting - Arsyad, Muhammad; Indah Fitria, Elsya; Farhan , M.Rizky; Maulana, Rahmad (CV RIFAINSTITUT, 2023)
The security technology that is widely used now is CCTV (closed-circuit television). CCTV can monitor and record all activities and events in a place at any time as the age develops the ability of CCTV to affect its selling price.the higher the CCTV specifications, the more expensive the price. therefore, many companies or campuses are struggling to determine the selection of the best CCTV brand The decision support system is one of the best ways to choose and solve these problems. and on this occasion the problem that can be completed properly, efficiently and effectively using the SAW method. from the results of CCTV calculations with brands in the range of 1,000,000 which have features that are more than 5 calculated weights 3, for applications used on CCTV calculated weights 2, for resolutions on CCTV cameras and image quality calculated weights 2. based on the final results that can be concluded that the best CCTV brand Hiksviksion Type DS-2DE4425IW-DE